Enhancing Complex Problem-Solving Skills through STEM-Based Spatial Geometry E-Modules - Megita Dwi Pamungkas; St Budi Waluya; Scolastika Mariani; Isnarto Isnarto; Fadhilah Rahmawati; Muhammad Noor Kholid; Pasttita Ayu Laksmiwati (Qubahan Academic Journal)
Learning spatial geometry is still abstract thereby it is boring and less meaningful. As a result, learning outcomes in terms of skills and cognitive aspects become less optimal. Currently, students are no longer rely on textbooks as a learning resource. E-module is digitally designed learning resources that support independent learning. The e-module would be integrated with STEM approach. STEM learning activities are very important and need to be familiarized in learning, because the activities help prospective teachers in building the concepts learned, as well as to practice solving complex real-world problems. The method was research and development using the ADDIE model. The research subjects were 78 students who were prospective mathematics teachers of Mathematics Education Study Program, Universitas Tidar. Data were collected by using observation sheets, interview guides, questionnaires, and complex problem-solving tests. There are three main results from the study; first, STEM-based spatial geometry E-module is declared to be strongly valid according to expert validators. Second, based on student responses, this e-module is practical and the third, based on the results of complex problem-solving skills test, this STEM-based spatial geometry e-module is effective.